THE EFFECTIVENESS OF DIRECT AND INDIRECT WRITTEN CORRECTIVE FEEDBACK IN EFL WRITING PERFORMANCE - Aridah Aridah (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
A long debate among scholars about the effect of feedback on students writing has never come to the end. Since Truscott (1996) claimed that error correction is not useful and even harmful, some researchers then come up with their findings in reaction to this claim (Hyland, 1998; Ferris, 2006; Ellis, et.al.. 2008; Sheen, 2010). They proved that feedback provision on students’ writing is still required because it is able to improve students’ writing. However, it is still a question, what type of feedback is most effective to improve students’ writing? This study aims to find out the effectiveness of direct and indirect feedback in EFL writing performance. Sixty-three students participated in this study, divided into three groups: 2 experimental groups and one control group. They were required to write five essays with different topics. Then, their papers were provided with different feedback: direct and indirect feedback for the experimental groups and peer feedback for the control group. When their papers were returned, the students were required to rewrite and revise their papers based on the corrections given by the teacher. The final versions of the papers were assessed in terms of content, organization, vocabulary, grammar, and mechanics to find out how effective one particular type of feedback improve the students’ writing performance. The findings revealed that the three types of feedback were able to improve the students’ writing performance.